Organization of Work on Promotion of a Healthy Lifestyle and Physical Culture: Potential of Continuing Education Complex - Krasulia , M. (New Collegium, 2021)
The article consider the issues of organizing the process of physical education in the context of lifelong education, the continuity of programs, methods and approaches in physical education, providing the relationship between the learning process at school and university. It is noted that continuity is the most important component of the educational process, a necessary condition for the unity and consistency of training. Achievement of continuity is possible only on condition of humanization and democratization of the educational process, competence-based and personal approach, as well as the integrity of physical education curricula. It is noted that the effective solution of these problems is impossible without providing a scientific approach to the organization of physical education classes, both at school and at the university, as well as without the formation of a physical educated personality, which is a problem within the framework of the traditional system of physical education. The main contradictions in the existing system of physical education and the components that negatively affect its development are analyzed. The pedagogical conditions for the formation of continuity are indicated. The article summarizes the experience of teachers of the Department of Physical Education and Sports of the Kharkiv Humanitarian University "People’s Ukrainian Academy", describes the distinctive features and positive aspects of the system of physical education formed at the academy, as well as possible directions for further improvement of the system of physical education in the context of continuous education. It is noted that on the basis of 20 years of work at the academy, the "Author’s integrated program of continuous training in physical education and the implementation of health-forming technologies at the Kharkiv Humanitarian University" People’s Ukrainian Academy" has been developed and implemented.